Agroforestry systems associated with natural regeneration: alternatives practiced by family-farmers of Tomé-Açu, Pará - Oliveira Neto, Mário; Alves, Livia de Freitas Navegantes; Schwartz, Gustavo (Sustainability in Debate, 2022)
The objective of this article was to analyze the benefits of Agroforestry Systems (AFSs) association with natural regeneration promoted by family farmers of Tomé-Açu, Pará, Brazil. Based on 46 previous interviews with family farmers, 12 of them were selected due to the presence of AFSs with different levels of tree species diversity, in which richness and diversity of tree species were taken into account. In addition, the measurement of the floristic variables was carried out. Results showed that 17% of the AFSs have natural regeneration corridors. This type of AFS has high species richness and diversity (Shannon-Weaner = 2.5), and its main characteristic is the presence of regeneration corridors of secondary forests. Therefore, farmers make production and forest regeneration compatible, and: a) maintain in their AFSs environmental services provided by regenerated secondary forests, b) ensure food security for their families, and c) they may have financial incomes from selling AFS products.